(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study provides an overview of the causes, strategies, and outcomes of social movements. Social movements and collective action are dynamic phenomena that emerge in response to perceived injustices, inequalities, and grievances within societies. The causes of social movements are diverse and encompass a range of social, economic, political, and cultural factors. Structural inequalities, including economic disparities, racial discrimination, gender inequality, and social injustices, serve as catalysts for mobilization, sparking collective action to challenge entrenched power structures and advocate for change. Political repression, authoritarian governance, cultural shifts, and technological advancements also play significant roles in shaping the emergence and trajectory of social movements. Social movements employ various strategies to advance their objectives, including nonviolent protest, political advocacy, legal action, community organizing, and media engagement. These strategies are often tailored to specific contexts and objectives, with movements leveraging their resources, networks, and collective power to raise awareness, mobilize support, and pressure authorities to address their grievances. The outcomes of social movements can be wide-ranging and multifaceted, encompassing policy changes, cultural shifts, institutional reforms, solidarity building, and empowerment of marginalized communities. Successful movements have achieved tangible policy reforms, such as the passage of legislation, implementation of social programs, and changes in government practices. Additionally, social movements contribute to broader cultural transformations by challenging prevailing norms, values, and attitudes, and promoting greater social awareness and acceptance of marginalized issues and identities.